Proteomic and Molecular Assessment of the Common Saudi Variant in ACADVL Gene Through Mesenchymal Stem Cells - Alfares, Ahmad; Alfadhel, Majid; Mujamammi, Ahmed; Alotaibi, Batoul; Albahkali, Sarah; Al Balwi, Mohammed; Benabdelkamel, Hicham; Masood, Afshan; Ali, Rizwan; Almuaysib, Amani; Al Mahri, Saeed; Mohammad, Sameer; et al. (Frontiers in Cell and Developmental Biology, 2020)
Very-long-chain acyl-coenzyme A dehydrogenase (VLCAD) is a coenzyme encoded by ACADVL that converts very-long-chain fatty acids into energy. This process is disrupted by c.65C>A; p.Ser22* mutation. To clarify mechanisms by which this mutation leads to VLCAD deficiency, we evaluated differences in molecular and cellular functions between mesenchymal stem cells with normal and mutant VLCAD. Saudi Arabia have a high incidence of this form of mutation. Stem cells with mutant VLCAD were isolated from skin of two patients. Metabolic activity and proliferation were evaluated. The Same evaluation was repeated on normal stem cells introduced with same mutation by CRISPR. Mitochondrial depiction was done by electron microscope and proteomic analysis was done on patients’ cells. Metabolic activity and proliferation were significantly lower in patients’ cells. Introducing the same mutation into normal stem cells resulted in the same defects. We detected mitochondrial abnormalities by electron microscopy in addition to poor wound healing and migration processes in mutant cells. Furthermore, in a proteomic analysis, we identified several upregulated or downregulated proteins related to hypoglycemia, liver disorder, and cardiac and muscle involvement. We concluded experimental assays of mutant ACADVL (c.65C>A; p.Ser22*) contribute to severe neonatal disorders with hypoglycemia, liver disorder, and cardiac and muscle involvement.